2022
DOI: 10.18196/ijnp.v5i2.13349
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Students’ Perception on Tutor Performance and Students’ Critical Thinking in PBL Online

Abstract: Background: The Covid-19 pandemic has influenced health education in many countries, including nursing education that moved to online learning.  It affects the tutor's performance and students' critical thinking skills, especially in online PBL tutorials. Tutor and nursing students have to re-adapt to a new online meeting atmosphere that previously had face-to-face meetings. There was no previous investigation into the effect of online PBL on tutor performance and nursing students’ critical thinking skills in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…In addition, the role-play videos created by students demonstrated that they could demonstrate civilityincivility in nursing education (Tahulending et al, 2021). However, Fahri's study concluded that students still required adjustment and adaptation to online learning tutorials and motivation to improve learning quality (Fahri & Musharyanti, 2022).…”
Section: Nursing Practicesmentioning
confidence: 99%
“…In addition, the role-play videos created by students demonstrated that they could demonstrate civilityincivility in nursing education (Tahulending et al, 2021). However, Fahri's study concluded that students still required adjustment and adaptation to online learning tutorials and motivation to improve learning quality (Fahri & Musharyanti, 2022).…”
Section: Nursing Practicesmentioning
confidence: 99%